STRATEGI PEMASARAN IKAN PATIN DAN PELUANG BINISNYA ( study kasus pada kolam ikan patin di daerah kabupaten Banyuain ) - Puspa Djuita (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
Every business that is established must face various kinds of challenges especially if the business is still new, but whatever type of challenge it inevitably has to be faced. Likewise, the aquaculture of pond catfish also has many obstacles and obstacles, one of which is that when the dry season arrives, many catfish die due to lack of water supply because their fish pond water supply comes from river water where when the dry season the river water will shrink .from the results of the analysis using simple linear regression results obtained that the semi-variable cost of catfish will increase along with an increase in the amount of catfish production, which results obtained Y = 348,959 + 27.61 (x). The fixed fee is Rp. 349,959, -, with a variable cost per unit of Rp. 27.61. Costs incurred in the cultivation of catfish is not so big.